Desain Tata Ruang Pendaftaran Rawat Jalan dan Rawat Inap di RS PKU Muhammadiyah Gamping - Muhammad Dudayev Caesar Putra (Universitas Duta Bangsa Surakarta, 2022)
The old outpatient registration room is narrow and the arrangement is inefficient, there is no bulkhead in the inpatient registration room to maintain the confidentiality of inpatient information. The location of the inpatient registration room is not strategic and close to the patient's public toilet, thus disturbing the inpatient registration officer. The lighting index at the outpatient registration is less than 100 lux, the room temperature is quite hot, the trolly and the fan behind the officer make the area of the outpatient registration area more narrower. The purpose of this study was to redesign the layout of outpatient and inpatient registration at PKU Muhammadiyah Gamping Hospital to be more ergonomic and in accordance with standards. This study used descriptive qualitative research. The unit of analysis in this study used 12 informants consisting of outpatient and inpatient registration officers. The results of this study is workspace ergonomics design of outpatient and inpatient registration room. Lighting with a minimum standard of 100 lux, temperature 21-24 ° C, with ventilation air circulation at least 15% of the area of ​​the room and also this design has been approved.